KEARIFAN MASYARAKAT DALAM PENGUNAAN API PADA KEGIATAN PENGOLAHAN LAHAN - Muhtar Muhtar; Fonny Rianawati; Rina Muhayah Noor Pitri (Universitas Lambung Mangkurat, 2019)
ABSTRACT The purpose of this research is to know the technique of using fire in the processing of the land and dig the local wisdom and traditional values of the community around the forest. The benefits of this research are as information to the community and related institutions (Dinas Kehutanan, Pertanian, Perkebunan) about community wisdom and the use of fire in the processing of land. Determination of location of research conducted by purposive sampling method that is deliberate determination of kare The village there is cultivation of land with the use of fire since their ancestors until now (hereditary). The respondent's intention was determined intentionally, with the number of samples taken as much as 54 respondents from 541 Head of Family or 10% from number of Head of Family which is considered to represent. Land management activities in Bangkalaan Dayak village are seen wisely because of the fire use techniques in land preparation by burning such as